A bibliographical survey on the use of ontologies in search interfaces - Dos Reis, Marcia Cristina [UNESP]; Ferneda, Edberto [UNESP] (Universidade Federal da Paraíba, 2019)
Search engines currently available on the Web, most based on the text box, have had little significant changes in the last years regarding the form of interaction with the user. Although they have become popular because of their simplicity, still present numerous problems related mainly to the researcher's dependence on knowledge in relation to the investigated subject, to difficulties in expressing a need for information through keywords, to the problems of ambiguity of language and to the inadequate composition of search terms. In this context, this research has as objective to analyze the literature on information retrieval interfaces and to raise concepts and characteristics that can subsidize the proposal of an interface model based on ontologies, with resources able to assist the user during the search and to minimize the problems observed. In order to reach the proposed objectives, the methodology adopted in this study had exploratory and bibliographic research, based on relevant authors of the area of Information Science. As results, it can be seen that ontologies have been widely discussed and adopted in several experiments related to the development of search interfaces more friendly and easy to be used, providing significant improvements in the information retrieval process. Such a resource can allow the user a direct interaction with the concepts of the researched domain and through them, allowing the choice of terms that best represent your need for information. In addition to the contributions and perspectives, it was also possible to identify the main challenges involved in the researched area.
Um levantamento bibliográfico sobre a utilização de ontologias em interfaces de busca
Keywords: Information retrieval; Ontology; Search interfaces